2014
DOI: 10.5723/kjcs.2014.35.4.103
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Variables Affecting Parenting Efficacy of North Korean Refugee Mothers : With a Focus on Marital Satisfaction, Social Support, and Acculturation

Abstract: The purpose of this study was to identify the variables affecting parenting efficacy of North Korean refugee mothers. The selected variables were marital satisfaction, social support, and acculturation. The participants consisted of 105 mothers who had defected from North Korea with preschool children living in Seoul, Gwangmyeong-si, and Gyeongsangnam-do provinces. The data thus collected were analyzed by descriptive statistics, t-tests, correlation, and multiple regression analysis. The results indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 13 publications
1
7
1
Order By: Relevance
“…With the rise in the number of North Korean refugees, problems related to their adaptation to South Korean society have also increased. North Korean refugee families experience psychological and economic burdens related to their family members left behind in North Korea, a lack of understanding and low intimacy in parent-child relations, economic difficulties and unstable jobs, stress in adapting to their life in South Korea, and traumas from their journey of defection [4]. In particular, the rise in the number of North Korean family refugees has increased the social interest in the nurturing and development of children [1,4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the rise in the number of North Korean refugees, problems related to their adaptation to South Korean society have also increased. North Korean refugee families experience psychological and economic burdens related to their family members left behind in North Korea, a lack of understanding and low intimacy in parent-child relations, economic difficulties and unstable jobs, stress in adapting to their life in South Korea, and traumas from their journey of defection [4]. In particular, the rise in the number of North Korean family refugees has increased the social interest in the nurturing and development of children [1,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Parent education programs that suit the characteristics of North Korean refugees have not been developed owing to the limited accessibility of the subjects, and research studies by only a few groups have analyzed the parenting experiences and characteristics of North Korean refugee parents, the effects of parenting behavior on children, and the demand for child education support [1,4,5,15]. Furthermore, limited studies have identified the predictors of parent-child relations or conducted programs aiming to improve those relations.…”
Section: Introductionmentioning
confidence: 99%
“…As previously mentioned, they are placed in very stressful environments even after resettlement, since North and South Korea have wide differences in their societies-social, cultural, political, educational, religious, etc. According to Park [5] (p. 2) study on the parenting of North Korean defectors, the stress of the NK refugee parents was found to be the main reason for dysfunctional parenting. NK refugee parents are not only exposed to constant stress, but they feel a lot of pressure related to their children's care and tend to negatively evaluate, criticize, and neglect their children [13] (p. 3).…”
Section: Influencing Factors Of Child Abuse In Migration Family 121mentioning
confidence: 99%
“…In fact, many NK refugee parents also feel they lack the ability to educate their children because the education methods and content between the two Koreas have changed during the period of division [7] (p. 2). Especially in the unusual context of 'migration' and 'transition', they are less confident about maternal roles and parenting abilities, defined as child-rearing effectiveness [5] (p. 2), [9] (p. 3), [13] (p. 3). Specific research such as this is essential in that unstable parenting efficiency of NK refugees' parents leads to an inconsistent and abusive parenting style, which can lead to various forms of abuse.…”
Section: Parenting Self-efficacy and Child Abusementioning
confidence: 99%
See 1 more Smart Citation